Micromineral nutritional requirements for weight gain in Canindé goats under grazing in the brazilian semiarid - doi: 10.4025/actascianimsci.v35i2.16731 - Silva, Cicilia Maria; Medeiros, Ariosvaldo Nunes de; Costa, Roberto Germano; Sales, Elzânia Pereira; Silva, Aderbal Marcos de Azevêdo; Lima Junior, Valdi de (Acta Scientiarum. Animal Sciences, 2012)
The purpose was to estimate the liquid requirements of Zn, Fe, Mn and Cu for weight gain in 46 castrated Canindé goats in grazing system in the Caatinga supplemented with 0, 0.5, 1 and 1.5% levels in relation to live weight. The animals had an initial average body weight of 15.76 ± 0.96 kg. Six animals were slaughtered at the onset of the experiment (16.1 ± 1.15 kg BW) and the rest (n = 40) were randomly distributed into one of the four levels of supplementation. The body composition (mg kg-1 EBW) varied from 8.47 to 9.09 mg Zn, 13.54 to 13.77 mg Fe, 6.34 to 6.36 mg Mn and 3.78 to 5.10 mg Cu, for Canindé goats with 15 and 25 kg BW, respectively, and the liquid requirements for gain (mg kg-1 BW gain) were estimated by the comparative slaughter method, and varied from 6.98 to 7.77 mg Zn; 10.20 to 10.72 mg Fe; 4.64 to 4.82 mg Mn and 4.28 to 5.96 mg Cu for the animals with BW varying from 15 to 25 kg, respectively. The liquid requirements of microminerals estimated in this research were inferior to the recommendations made by international committees.